Effect of experimental conditions on nano-indentation response of low density polyethylene (LDPE). Issue 7 (3rd July 2019) - Yasin, Saima; Shakeel, Ahmad; Iqbal, Tanveer; Ahmad, Fazeel; Mehmood, Hamayoun; Luckham, Paul F.; Ullah, Nehar
Abstract: Nano-indentation is an interesting tool for analyzing nano-scale mechanical properties. The analysis of nano-mechanical properties as a function of experimental conditions is very critical for designing engineering components. In this study, nano-indentation experiments were performed by considering different values of amplitude (1, 5, 10 nm), frequency (11.2, 22.5, 45 Hz), strain rate (0.02, 0.05, 0.1, 0.2, 1 s −1 ), peak load (10, 30, 100 mN) and hold time (1, 3, 5, 10, 20, 50, 100 sec) to analyze their effect on the mechanical properties of LDPE. The results showed that the effect of amplitude and frequency on the nano-mechanical properties of LDPE were negligible. Load-displacement curves displayed a shift towards higher indentation depths along with a decrease in peak load from 20.6 to 14.8 mN by having a decrease in strain rate from 1 to 0.02 s −1 . Elastic modulus and hardness values exhibited a decrease with an increase in hold time. Logarithmic creep model was used to fit the experimental data of creep as a function of holding time which showed good agreement (r 2 ≥ 0.97) with the experimental values. Recommended holding times are also suggested to eliminate the creep and nose problem in order to achieve high accuracy in measurements.